Factors responsible for formation of severity of inflammatory parodontal diseases in adolescent girls with menstrual dysfunction - Kliuchka, Ye. A.; Sokolova, I. I.; Tuchkina, I. A.; Piontkovskaya, O. V. (Journal of Education, Health and Sport, 2017)
Determining the factors of formation of severity of parodontal inflammatory diseases (PID) in adolescent girls with menstrual dysfunction (MD) makes it possible to determine the predictors of severity of PID and, on this basis, to develop differentiated methods for their prevention. The aim. To determine the factors responsible for formation of PID severity in adolescent girls with MD. The materials and methods. The following data were studied in adolescent girls with MD with varying severity of PID: obstetric and genealogical anamnesis, lifestyles of adolescents, indices of oral hygiene, dental status, densitometry, content of CA ++ and sIgA in saliva, lysozyme and urease activity in saliva, cytobiophysical potential of buccal epithelium nuclei. The findings. In patients with more severe course of PID, in comparison to milder course of PID, there was determined a more significant degree of weakened heredity in relation to chronic dental and somatic pathology, unfavorable course of pregnancy and childbirth, violations of a healthy lifestyle and oral hygiene in adolescents, anomalies in the development of dentoalveolar system, dysbiosis of oral cavity, reduced local and systemic immunoresistance. Conclusion: The determined predictors of the severity of PID in adolescent girls with MD make it possible to develop differentiated methods for their prevention.